Sustainable Development of ZnSO₄·H₂O and ZnO via Gelatin-Based Colloids for Advanced Dye Photodegradation - Ulfa, Maria; Aziza, Hilmia (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
This study looks at how to sustainably develop ZnSO₄·H₂O (Gunningite) and ZnO (Wurtzite) nanoparticles using gelatin-based colloids, focusing on their ability to break down dyes. Zinc acetate and zinc sulfate heptahydrate were used as starting materials, with gelatin helping to stabilize the process. After heating at 550 °C for 4 hours, the nanoparticles were analyzed for their surface area and composition. Gunningite had a higher surface area of 61.5 m²/g, compared to Wurtzite’s 11.4 m²/g. Elemental analysis showed Gunningite contained 71% zinc, 21% oxygen, and 2% sulfur, while Wurtzite had 69% zinc and 31% oxygen. The photocatalytic activity was tested by degrading methylene blue under UV light. Gunningite had better results, achieving 87% degradation compared to Wurtzite's 72%. This was due to Gunningite’s larger surface area and smaller particle size, making it more effective for treating dye wastewater. Future studies could explore larger-scale synthesis and industrial uses. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).